Pengaruh Manajemen Berbasis Nilai terhadap Keputusan Divestasi dengan Kepentingan Pemegang Saham dan Kepentingan Manajemen sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Manufaktur Sektor Barang Konsumsi di Bursa Efek Indonesia Periode 2018 - 2022 - Salma, Devhaura; Bastian, Elvin; Sabaruddinsah, Sabaruddinsah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The research explores the effect of value-based management on divestment decisions with the interests of shareholders and management interests as moderating variables. The population under study includes consumer goods manufacturing firms listed on the Indonesia Stock Exchange over the period 2018 to 2022. This research utilizes purposive sampling for data collection, obtaining 36 companies with 96 data pointsThe research utilizes a quantitative approach, relying on secondary data from annual reports and financial statements of consumer goods manufacturing companiesobtained from the Indonesia Stock Exchange for the period of 2018-2022. This study uses the moderated regression analysis (MRA) technique with IBM SPSS 25 application. The results show that value-based management has a positive influence on divestment decisions, indicating that value-based management can enhance divestment decisions.The interests of shareholders cannot moderate value-based management in relation to divestment decisions. The interests of management, which are reinforce divestment decision-making, can thus moderate value-based management in relation to divestment decisions.